I-PLA(2) Activation during Apoptosis Promotes the Exposure of Membrane Lysophosphatidylcholine Leading to Binding by Natural Immunoglobulin M Antibodies and Complement Activation - Kim, Sun Jun (The Rockefeller University Press, 2002)
Deficiency of serum immunoglobulin (Ig)M is associated with the development of a lupus-like disease in mice. Recent studies suggest that classical complement components facilitate the clearance of apoptotic cells and that failure to do so predisposes mice to lupus. Since IgM is a potent activator of the classical complement pathway, we examined IgM binding to dying cells. IgM, but not IgG, bound to apoptotic T cells through the Fab′ portion of the antibody. Exposure of apoptotic cell membranes to phospholipase (PL) A2 increased, whereas PLD reduced, IgM binding and complement activation. Absorption studies combined with direct plate binding assays, revealed that IgM antibodies failed to bind to phosphatidyl lipids, but did recognize lysophosphatidylcholine and the phosphorylcholine head group. Both iPLA(2) and cPLA(2) are activated during apoptosis. Since inhibition of iPLA2, but not cPLA2, attenuated IgM binding to apoptotic cells, these results strongly suggest that the endogenous calcium independent PLA(2), iPLA(2), is involved in the hydrolysis of plasma membrane phospholipids and exposure of the epitope(s) recognized by IgM. We propose that recognition of dying cells by natural IgM antibodies is, in part, responsible for complement activation on dying cells leading to their safe clearance.